IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN GEOGRAFI DI SMA NEGERI 4 WATAMPONE - Eka Damayanti, Defrianti Kartika (LaGeografia, 2018)
This study aims to find out: 1) To find out how the 2013 curriculum implementation on Geography subjects at SMA 4 Watampone, 2) To find out what barriers teachers face in implementing the 2013 curriculum in 4 watampone public high schools, 3) For find out what efforts are made by the teacher to overcome obstacles in the implementation of the 2013 Curriculum on geographic subjects at SMA 4 Watapone. Data collection uses interviews, documentation and observation. The results of the study show that: 1). Implementation is the implementation or application carried out by a teacher in creating and growing various activities in accordance with the plans that have been programmed to achieve previously determined. The implementation of the 2013 curriculum at Watampone 4 Public High School has been running but it is still not in accordance with the standard set by the government, because in implementing the 2013 curriculum. Judging from the standard learning process that uses a scientific approach and learning processes that apply 5 M have not run properly, and are seen again from the existing facilities in the school, it is not yet complete in accordance with the requirements of the government that has been fixed, right. 2). Obstacles or constraints faced by teachers in the process of implementing the 2013 curriculum on Geogarfi subjects at SMA 4 Watampone namely the completeness of learning tools consisting of learning implementation plans (RPP), teaching material materials, student worksheets (LKPD), learning media , evaluation and assessment of facilities and infrastructure. 3). Teachers' Efforts to Overcome Obstacles in the Implementation of the 2013 Curriculum on Geography Learning in Watampone 4 High School, namely 1) Geography teachers are involved directly in 2013 curriculum development. 2) Evaluation of KTSP as the previous curriculum is needed. 3) Material adjustment geography in the 2013 curriculum.4) More intensifying geography teacher training in the implementation of the 2013 curriculum.5) Balanced geographic learning between theory and field learning, 6) Changing the mindset to the 2013 Curriculum mindset.7) Striving for school principals to be more attentive and motivating teachers, 9) improving facilities and infrastructure, 10) Making the best use of reference book resources, 11) Motivating oneself to be more enthusiastic, 12) Improving socialization of relations between fellow teachers, 13) Following socialization and training related to 2013 Curriculum is more active. etc.